Thermal response tests : influence of convective flow in groundwater filled borehole heat exchanger - Gustafsson, Anna-Maria (Luleå tekniska universitet, Arkitektur och vatten, 2010)
The main objective of this doctorial thesis was to investigate how thermally induced movements in the groundwater (natural convective flow) may influence the heat transport in borehole and surrounding bedrock in a groundwater filled borehole heat exchanger system. The purpose was also to determine if thermal response tests could be used to detect the convective influence and the effect on evaluated heat transfer parameters, effective bedrock thermal conductivity and borehole thermal resistance. In order to increase the knowledge about the natural convective influence in groundwater filled borehole heat exchangers, numerical 3D simulations in the computer fluid dynamic (CFD) software Fluent were conducted. It was shown that the thermally induced convective flow influenced the borehole thermal resistance independently of bedrock characteristics (solid or fractured). A larger convective heat flow (dependent on density gradient) resulted in a lower resistance. The density gradient and thereby the convective flow are affected by the water temperature level and the used heat injection or extraction rate. At a water temperature around 4ºC (maximum density), the borehole thermal resistance had its maximum value resulting in values close to stagnant water. In other working conditions the heat transfer could be up to 2.5 times greater than that of stagnant water. This was further investigated and confirmed by in-situ thermal response tests in two boreholes at the campus of Luleå University of Technology. Several multi-injection rate thermal response tests were performed, which is a test protocol where several test periods are performed in a row using different heat injection rates. With this protocol it was shown that natural convective flow may be seen to affect both the borehole thermal resistance and effective bedrock thermal conductivity. For the bedrock thermal conductivity it was shown that the convective influence was seen only for fractured bedrock. A larger convective heat flow resulted in a higher effective ...